Memahami Tujuan Pendidikan Islam, Multi, Inter dan Transdisipliner - Mushofa Mushofa; Syaifuddin Sabda; Ridhahani Fidzi; Husnul Yaqin (Syntax Corporation Indonesia, 2024)
This paper discusses understanding the purpose of Islamic education in a multi, inter and transdisciplinary approach. This issue is very urgent, given the importance of understanding the teachings of Islam in a comprehensive manner. Islam as a religion does not only teach the realm of ubudiyah, but also mu'amalah. It is in the realm of mu'amalah that humanity is faced with the complexity of life problems that must be resolved. Especially in modern times like today, an approach from various scientific angles is needed. This research is in the form of library research with a qualitative descriptive approach. After the study, it is concluded that Islamic education is not just a transfer of knowledge, but also a holistic process that forms individuals with noble character. In the context of an increasingly advanced life, Islamic education as a scientific discipline cannot stand alone in solving problems in society. There is a need for multi, inter and transdisciplinary science, so scientific integration here is very necessary.